Does financial development drive private investment in Ghana? - Daniel Sakyi; Micheal Kofi Boachie; Mustapha Immurana (Economies, 2016)
There is ample evidence from economic growth literature that investment accelerates economic growth and development of developing countries, of which Ghana is not an exception. Based on this, recent growth and development policies in Ghana have focused more on encouraging private sector investment through the development of the financial sector. This paper investigates the short- and long-run impact of financial development on private investment in Ghana for the years 1970-2014. Additionally, to find out whether the measurement of financial development matters for private investment, several indicators of financial development are used. The results, based on the ARDL bounds testing approach to cointegration, suggest that financial development has not been a key driver of private investment in the long run, while, in the short run, the effect of financial development on private investment depends on how financial development is measured. Given these results, policy makers should be circumspect regarding the choice of financial development indicator used as a policy instrument in the design and implementation of private investment policies for Ghana.
Keywords: C13; C32; E22; E44; 330; financial development; private investment; ARDL; Ghana